2020
DOI: 10.1186/s12888-020-2481-0
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of web-assisted self-help for parents of children with ADHD (WASH) – a three-arm randomized trial under field/routine care conditions in Germany

Abstract: Background: Current clinical guidelines recommend parent management training (PMT) in the treatment of attention-deficit/hyperactivity disorder (ADHD) and oppositional defiant disorder (ODD). However, (a) a lack of supply and (b) structural barriers to attending and continuing face-to-face PMT restrict the access to this training. The main purpose of this study is to investigate the efficacy of online PMT in decreasing ADHD symptoms and oppositional behavior problems and to evaluate the effects of additional t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 29 publications
0
7
0
1
Order By: Relevance
“…A review has concluded that telemedicine was cost-effective for children and suggested that research should also be conducted in adults with ADHD [ 75 ]. In the pipeline, there is a randomized controlled trial underway to investigate the efficacy of a web-assisted self-help programme for parents of children with ADHD [ 76 ].…”
Section: Resultsmentioning
confidence: 99%
“…A review has concluded that telemedicine was cost-effective for children and suggested that research should also be conducted in adults with ADHD [ 75 ]. In the pipeline, there is a randomized controlled trial underway to investigate the efficacy of a web-assisted self-help programme for parents of children with ADHD [ 76 ].…”
Section: Resultsmentioning
confidence: 99%
“…The family environment should be also considered because of its influence in the emergence of problematic gaming behavior [ 99 , 100 ] and the persistence of GD symptoms over time [ 20 ]. Therefore, even when video games are considered for ADHD treatment, parent training and individual psychological interventions should always be provided within the framework of a multimodal approach and considering the effectiveness of specialized psychological programs for patients with GD [ 101 , 102 , 103 ] and the parent training for ADHD [ 104 ] even when performed online [ 105 ]. Finally, since a protracted exposure to addictive agents has been shown to result in disruptions in several circuits responsible for maintaining addiction due to neural adaptations, neurocircuit-based interventions could also be taken into account, thanks to their potential to target the neuroanatomical structures that work as ‘nodes’ within these circuits [ 106 ], with protocols specifically created for behavioral addictions [ 107 ].…”
Section: Discussionmentioning
confidence: 99%
“…Such an approach is foreshadowed in calls for tiered child mental health care involving digital tools in Brazil (Mari et al, 2021). BPT programs have been offered online in other countries with emerging empirical support (Döpfner et al, 2020;DuPaul et al, 2018;Williams & Beidas, 2019). Many Brazilians access information online with cell phones, which are widely available even amongst low-income communities (de Araujo & Reinhard, 2019;Nemer, 2018).…”
Section: Discussionmentioning
confidence: 99%